A novel clade of Prochlorococcus found in high nutrient low chlorophyll waters in the South and Equatorial Pacific Ocean - West, Nyree J; Lebaron, Philippe; Strutton, Pete G; Suzuki, Marcelino T (The ISME Journal, 2011)
A novel high-light (HL)-adapted Prochlorococcus clade was discovered in high nutrient and low chlorophyll (HNLC) waters in the South Pacific Ocean by phylogenetic analyses of 16S ribosomal RNA (rRNA) and 16S–23S internal transcribed spacer (ITS) sequences. This clade, named HNLC fell within the HL-adapted Prochlorococcus clade with sequences above 99% similarity to one another, and was divided into two subclades, HNLC1 and HNLC2. The distribution of the whole HNLC clade in a northwest to southeast transect in the South Pacific (HNLC-to-gyre) and two 8°N to 8°S transects in the Equatorial Pacific was determined by quantitative PCR using specific primers targeting ITS regions. HNLC was the dominant HL Prochlorococcus clade (2–9% of bacterial 16S rRNA genes) at the three westernmost stations in the South Pacific but decreased to less than 0.1% at the other stations being replaced by the eMIT9312 ecotype in the hyperoligotrophic gyre. The highest contributions of HNLC Prochlorococcus in both Equatorial Pacific transects along the latitudinal lines of 170°W and 155°W were observed at the southernmost stations, reaching 16 and 6% of bacterial 16S rRNA genes, respectively, whereas eMIT9312 dominated near the Equator. Spearman Rank Order correlation analysis indicated that although both the HNLC clade and eMIT9312 were correlated with temperature, they showed different correlations with regard to nutrients. HNLC only showed significant correlations to ammonium uptake and regeneration rates, whereas eMIT9312 was negatively correlated with inorganic nutrients.